A critical role for donor‐derived IL‐22 in cutaneous chronic GVHD. Issue 4 (24th October 2017) - Gartlan, Kate H.; Bommiasamy, Hemamalini; Paz, Katelyn; Wilkinson, Andrew N.; Owen, Mary; Reichenbach, Dawn K.; Banovic, Tatjana; Wehner, Kimberly; Buchanan, Faith; Varelias, Antiopi; Kuns, Rachel D.; Chang, Karshing; et al.
Abstract : Graft‐versus‐host disease (GVHD) is the major cause of nonrelapse morbidity and mortality after allogeneic stem cell transplantation (allo‐SCT). Prevention and treatment of GVHD remain inadequate and commonly lead to end‐organ dysfunction and opportunistic infection. The role of interleukin (IL)‐17 and IL‐22 in GVHD remains uncertain, due to an apparent lack of lineage fidelity and variable and contextually determined protective and pathogenic effects. We demonstrate that donor T cell–derived IL‐22 significantly exacerbates cutaneous chronic GVHD and that IL‐22 is produced by highly inflammatory donor CD4 + T cells posttransplantation. IL‐22 and IL‐17A derive from both independent and overlapping lineages, defined as T helper (Th)22 and IL‐22 + Th17 cells. Donor Th22 and IL‐22 + Th17 cells share a similar IL‐6–dependent developmental pathway, and while Th22 cells arise independently of the IL‐22 + Th17 lineage, IL‐17 signaling to donor Th22 directly promotes their development in allo‐SCT. Importantly, while both IL‐22 and IL‐17 mediate skin GVHD, Th17‐induced chronic GVHD can be attenuated by IL‐22 inhibition in preclinical systems. In the clinic, high levels of both IL‐17A and IL‐22 expression are present in the skin of patients with GVHD after allo‐SCT. Together, these data demonstrate a key role for donor‐derived IL‐22 in patients with chronic skin GVHD and confirm parallel but symbiotic developmental pathways of Th22 and Th17 differentiation. Abstract : This study demonstrates a tissue‐specific role for IL‐22 in mediating chronic cutaneous graft‐versus‐host disease, confirming parallel but symbiotic pathways of Th22 and Th17 differentiation, and highlights potential new therapeutic approaches.